Mechanisms of Social Consolidation in the Network Society - L. A. Bobova (Vestnik MGIMO-Universiteta)
During the last five years the world has seen the emergence of mass global and regional social movements outside of institutional structures representing open systems with a spontaneous nature. These social movements do not have any tangible hierarchy and leaders; information within the movement activity is spread virally and mainly using new electronic communication tools - namely, mass self-communication constituting spaces of communication autonomy beyond the control of governments. A feature of the new type of social movements is their emergence in virtual space. Such mass movements manifest intensified consolidation processes in the modern society - due to fundamentally new factors. New practical mechanisms of consolidation amid an increase in the proportion of young people in countries are directly linked with technological developments that influenced in essence communication and changes in the established modern informational society. Virtual mass self-communication becomes the main practical mechanism for social consolidation in the modern informational society. The consolidation process intensifies due to government legitimacy crisis and loss of public trust in government and indicates an emergence of a new form of a civil society.